The science and art of testing in ice hockey: a systematic review of twenty years of research - Bournival, M.; Martini, G.; Trudeau, F.; Lemoyne, J. (Frontiers in Sports and Active Living, 2023)
Introduction: Ice hockey is a complex sport requiring multiple athletic and technical attributes. Considering the variety of tests developed, on-ice testing protocols have been created to measure the physiological and mechanical attributes associated with performance. To our knowledge, a lack of technical resources exists to help stakeholders opt for on-ice protocols from among those developed. It becomes crucial for researchers and practitioners to select relevant and context-specific procedures. This systematic review of the literature outlines an inventory of the on-ice tests that have been used in the domain of ice hockey research over the last twenty years, and summarize protocols mostly used in major athletic components.